Mixed programming metaphors in a shared dataspace model of concurrency - Roman, G.-C.; Cunningham, H.C. (IEEE transactions on software engineering, 1990)
A simple language called Swarm is used as a vehicle for the investigation of the shared dataspace approach to concurrent computation. An important feature of Swarm is its ability to bring a variety of programming paradigms under a single, unified model. In a series of related examples Swarm's capacity to express shared-variable, message-passing, and rule-based computations; to specify synchronous and asynchronous processing modes; and to accommodate highly dynamic program and data structure is explored. Several illustrations make use of a programming construct unique to Swarm, the synchrony relation and explain how this feature can be used to construct dynamically structured, partially synchronous computations. An overview of the Swarm programming notation, an examination of Swarm programming strategies via a series of related example programs, and a discussion of the distinctive features of the shared dataspace model are given. A formal operational model for Swarm is presented.< >